Ketamine; A better anti-depressant? An animal study evaluating the efficacy of citalopram, ketamine and their combination in animal models of depression - Salim Sheikh; Pankaj Sonone; Veena Verma; Chakar Dhar Tripathi; Bushra Ahmed Karim; Girish Gulab Meshram (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2021)
Background: Despite the availability of vast group of drugs, treatment of depression still remains unsatisfactory, largely due to differential efficacy of antidepressants at adequate doses resulting in treatment refractive depression. In addition, serious adverse effects of anti-depressants also lead to early withdrawal from treatment. One more important concern is the therapeutic lag of nearly 3-4 weeks, before some appreciable clinical effect. Therefore, newer agents with good safety profile, rapid onset of action and with substantial benefits in treating patients who are either refractory or resistant to conventional therapy, need to be explored. Methods: 8 groups of 6 mice each were evaluated for anti-depressant effect in Tail Suspension Test and Forced Swim Test. Treatment used was normal saline (control), citalopram, ketamine and combination of ketamine with citalopram. Results: Citalopram decreased the immobility time in both models but it was not significant in FST. Significant decrease in immobility time was observed in ketamine treated mice in both models. Ketamine and citalopram combination also decreased the immobility time significantly. Conclusion: Ketamine have an antidepressant activity of its own, as shown in both TST & FST models. Additionally, it also potentiated the antidepressant effect of citalopram, which could be attributed to possible involvement of NMDA receptors and its interaction with the monoaminergic system.